Fermentative Bacteria Influence the Competition between Denitrifiers and DNRA Bacteria - van den Berg, Eveline M.; Elisário, Marina P.; Kuenen, J. Gijs; Kleerebezem, Robbert; van Loosdrecht, Mark C. M. (Frontiers in Microbiology, 2017)
Denitrification and dissimilatory reduction to ammonium (DNRA) are competing nitrate-reduction processes that entail important biogeochemical consequences for nitrogen retention/removal in natural and man-made ecosystems. The nature of the available carbon source and electron donor have been suggested to play an important role on the outcome of this microbial competition. In this study, the influence of lactate as fermentable carbon source on the competition for nitrate was investigated for varying ratios of lactate and nitrate in the influent (Lac/N ratio). The study was conducted in an open chemostat culture, enriched from activated sludge, under strict anoxia. The mechanistic explanation of the conversions observed was based on integration of results from specific batch tests with biomass from the chemostat, molecular analysis of the biomass enriched, and a computational model. At high Lac/N ratio (2.97 mol/mol) both fermentative and respiratory nitrate reduction to ammonium occurred, coupled to partial oxidation of lactate to acetate, and to acetate oxidation respectively. Remaining lactate was fermented to propionate and acetate. At a decreased Lac/N ratio (1.15 mol/mol), the molar percentage of nitrate reduced to ammonium decreased to 58%, even though lactate was supplied in adequate amounts for full ammonification and nitrate remained the growth limiting compound. Data evaluation at this Lac/N ratio suggested conversions were comparable to the higher Lac/N ratio, except for lactate oxidation to acetate that was coupled to denitrification instead of ammonification. Respiratory DNRA on acetate was likely catalysed by two Geobacter species related to G. luticola and G. lovleyi. Two Clostridiales members were likely responsible for lactate fermentation and partial lactate fermentation to acetate coupled to fermentative DNRA. An organism related to Propionivibrio militaris was identified as the organism likely responsible for denitrification. The results of this study clearly show that not only the ratio of available substrates, but also the nature of the electron donor influences the outcome of competition between DNRA and denitrification. Apparently, fermentative bacteria are competitive for the electron donor and thereby alter the ratio of available substrates for nitrate reduction.